The Concept of Professional Learning Community By Teacher Group in Developing Religious Work Culture At LPIT Nurul Fikri Juwana - Rahmawati, Tri (Pascasarjana IAIN Kudus, 2021)
AbstractThis study aims to analyze and understand the concept of a professional learning community by a group of teachers in developing a religious work culture to improve the quality of teacher and employee performance as a form of success for educational institutions at LPIT Nurul Fikri Juwana. This study uses a qualitative approach to the type of field research (field research). The results showed that the concept of Professional Learning Community in developing a religious work culture at the Nurul Fikri Integrated Islamic Education Institute can be done through discussion, example, spontaneous habituation, routine activities and conditioning. However, in the implementation of the Professional Learning Community, there are some obstacles, including the difficulty of controlling the rapid development of information technology, the different behavior of teachers and students, the lack of balance between the school environment, the family environment and the community environment which cause the values of religious work culture are not implemented optimally. In addition, the implementation of the Professional Learning Community concept in developing a religious work culture requires a long process, so the results cannot be felt immediately. Linking individual learning to stakeholder learning is a basic element of building a learning community. Embedded in the learning community is a concept that if all stakeholders learn, the school will develop to meet its future and also a religious work culture in everyday life so that the community as education customers are satisfied with the results of planting religiosity to students.AbstrakPenelitian ini bertujuan untuk menganalisis dan memahami konsep professional learning community oleh kelompok guru dalam mengembangkan budaya kerja religius untuk meningkatkan kualitas kinerja guru dan karyawan sebagai bentuk kesuksesan lembaga pendidikan di LPIT Nurul Fikri Juwana. Penelitian ini menggunakan pendekatan kualitatif jenis penelitian lapangan (field research). Hasil penelitian menunjukkan bahwa konsep Professional Learning Community dalam mengembangkan budaya kerja religius di Lembaga Pendidikan Islam Terpadu Nurul Fikri dapat dilakukan melalui diskusi, keteladanan, pembiasaan spontan, kegiatan rutin dan pengkondisian. Namun dalam implementasinya Professional Learning Community masih ditemukan kendala diantaranya yaitu sulitnya mengontrol perkembangan teknologi informasi yang sangat pesat, adanya perilaku guru serta peserta didik yang berbeda, kurang adanya keseimbangan antara lingkungan lembaga sekolah, lingkungan keluarga dan lingkungan masyarakat yang mengakibatkan nilai-nilai budaya kerja religius tidak terimplementasikan secara maksimal. Selain itu implementasi konsep Professional Learning Community dalam mengembangkan budaya kerja religius membutuhkan proses yang panjang, sehingga tidak bisa langsung dirasakan hasilnya. Mengaitkan pembelajaran individual dengan pembelajaran stakeholder merupakan elemen dasar membangun komunitas pembelajaran. Tertanam di dalam komunitas pembelajaran sebuah konsep bahwa apabila seluruh stakeholder belajar, maka sekolah pun akan berkembang untuk menyongsong masa depannya dan tentunya pula dalam mengembangkan budaya kerja religius dalam kehidupan sehari-hari sehingga masyarakat sebagai pelanggan pendidikan puas dengan hasil penanaman religiusitas kepada peserta didik.